Twin Models of Environmental and Genetic Influences on Pubertal Development, Salivary Testosterone and Estradiol in Adolescence - Grotzinger, Andrew D. (Clin Endocrinol (Oxf), 2017)
OBJECTIVE: Research on sources of variation in adolescent’s gonadal hormone levels is limited. We sought to decompose individual differences in adolescent testosterone, estradiol and pubertal status, into genetic and environmental components. DESIGN: A sample of male and female adolescent twins from the greater Austin and Houston areas provided salivary samples, with a subset of participants providing longitudinal data at two waves. PARTICIPANTS: The sample included 902 adolescent twins, 49% female, ages 13–20 years (M = 15.91) from the Texas Twin Project. Thirty-seven percent (37%) of twin pairs were monozygotic; 30% were same-sex dizygotic pairs; and 33% were opposite-sex dizygotic pairs. MEASUREMENTS: Saliva samples were assayed for testosterone and estradiol using chemiluminscense-immunoassays. Pubertal status was assessed using self-report. Biometric decompositions were performed using multivariate quantitative genetic models. RESULTS: Genetic factors contributed substantially to variation in testosterone in males and females in the follicular phase of their menstrual cycle (h(2) = 60% and 51%, respectively). Estradiol was also genetically influenced in both sexes, but was predominately influenced by non-shared environmental factors. The correlation between testosterone and estradiol was mediated by a combination of genetic and environmental influences for males and females. Genetic and environmental influences on hormonal concentrations were only weakly correlated with self-reported pubertal status, particularly for females. CONCLUSIONS: Between-person variability in adolescent gonadal hormones and their inter-relationship reflects both genetic and environmental processes, with both testosterone and estradiol containing sizeable heritable components.